The Philosophy of Balinese Text I Sugih Teken I Tiwas: Systemic Functional Linguistics - I Ketut Suardana; Nidya Fitri (Balai Bahasa Provinsi Bali, 2024)
This research investigated the philosophy of Text I Sugih Tekẻn I Tiwas ‘the rich and the poor’ from Systemic Functional Linguistics. The data source was taken from Pupulan Satwa Bali ‘Ba-linese narrative text collection’ realized with Balinese text. This research used qualitative with grounded theory. The result of the research indicated that; elaboration verbs were used to state advantages for I Tiwas, extension verbs were used to elaborate on I Tiwas’s disadvantages, and enhancement verbs were used to elaborate I Sugih’s ambition. The philosophy of the text is re-lated to Hindu philosophy called Karma Pala ‘cause and effect law’ involving; how to humanize others, how to be a creative person, and how to use language properly. This research has signif-icance for linguistics research, namely semantics, semiotics, language philosophy, and dis-course.